Does brand spelling influence memory? The case of auditorily presented brand names - Luna, David; Carnevale, Marina; Lerman, Dawn (Journal of Consumer Psychology, 2013)
AbstractWe present a framework based on psycholinguistic theory to explain how individuals spell auditorily‐presented information. We use the framework to predict and test how spelling‐related characteristics of brand names and factors related to the context in which brand names are presented (e.g., spelling primes) will make the brands more or less memorable. Further, we reveal the process through which spelling‐related linguistic variables influence brand recall: the dual‐code (both written and auditory) that results from spelling a brand correctly leads to greater ability to later recall the brand. Our framework identifies two routes that interact when individuals have to transcribe a brand: the lexical (top‐down) route and the sublexical (bottom‐up) route.